Indikator Membangun Good Cooperative Governance, untuk Menumbuhkan Kepercayaan Masyarakat terhadap Koperasi, Studi di Kota Medan - Nainggolan, Karlonta; Parulian, Tohap; Siregar, Ali Usman (Jurnal Aplikasi Manajemen, 2016)
Abstract:this study aims to identify indicators to develop GCG, basedon principles and values of cooperative. Data were analized by second order CFA, then interpreted with Important Performance Analysis. We use high Î» â‰¥ 0.50 and high x â‰¥ 3.50 to measure the level of understanding and application of indicators. The result of analysis indicate, six out of twenty indicators, are pretended to be unimportant factors by most of Managers, ten indicators are indicated as important indicators, but its implementation is still low, while four indicators are already running well. Learning from the result of analysis, and what we tried to understand during the research, as well as information and recommendation gathered from FGD, we concluded that to developed GCG based on cooperative principles and values, are education, and character building for all stakeholdersÂ